Methodological issues in economic evaluations of disease prevention and health promotion: an overview of systematic and scoping reviews - Yana Seleznova; Adrienne Alayli; Stephanie Stock; Dirk Müller (BMC, 2021)
Abstract Background We aimed to provide a comprehensive overview of methodological challenges in economic evaluations of disease prevention and health promotion (DPHP)-measures. Methods We conducted an overview of reviews searching MEDLINE, EMBASE, NHS Economic Evaluation Database, Database of Promoting Health Effectiveness Reviews, Cochrane Database of Systematic Reviews (CDSR) and Database of Promoting Health Effectiveness Reviews (DOPHER) (from their inception to October 2021). We included both systematic and scoping reviews of economic evaluations in DPHP addressing following methodological aspects: (i) attribution of effects, (ii) outcomes, (iii) inter-sectoral (accruing to non-health sectors of society) costs and consequences and (iv) equity. Data were extracted according to the associated sub-criteria of the four methodological aspects including study design economic evaluation (e.g. model-based), type/scope of the outcomes (e.g. outcomes beyond health), perspective, cost categories related to non-health sectors of society, and consideration of equity (method of inclusion). Two reviewers independently screened all citations, full-text articles, and extracted data. A narrative synthesis without a meta-analysis or other statistical synthesis methods was conducted. Results The reviewing process resulted in ten systematic and one scoping review summarizing 494 health economic evaluations. A lifelong time horizon was adopted in about 23% of DPHP evaluations, while 64% of trial-based evaluations had a time horizon up to 2 years. Preference-based outcomes (36%) and non-health outcomes (8%) were only applied in a minority of studies. Although the inclusion of inter-sectoral costs (i.e. costs accruing to non-health sectors of society) has increased in recent years, these were often neglected (between 6 and 23% depending on the cost category). Consideration to equity was barely given in economic evaluations, and only addressed in six of the eleven reviews. Conclusions Economic evaluations of DPHP measures give only little attention to the specific methodological challenges related to this area. For future economic DPHP evaluations a tool with structured guidance should be developed. This overview of reviews was not registered and a published protocol does not exist.